Nickel Downstreaming in Indonesia: Reinventing Sustainable Industrial Policy and Developmental State in Building the EV Industry in ASEAN - Lahadalia, Bahlil; Wijaya, Chandra; Dartanto, Teguh; Subroto, Athor (JAS (Journal of ASEAN Studies), 2024)
The developmental state concept, which entails proactive government support for economic structural transformation, remains contentious today. Some scholars vigorously argue that government intervention in the economy was indispensable to the success of East Asian countries, whereas others are critical of the practice, arguing that it tends to neglect sustainability dimensions and contending that government intervention in the market is often unwarranted. In this study, the authors analyse how Indonesia’s nickel ‘downstreaming’ strategy represents a new developmental state model that considers the aforementioned discourse on the merit of industrial policy. The new model aligns the classical developmental state concept with the need to address pressing environmental and social concerns, which are widely recognized as being of paramount importance. Through an integrative literature review and secondary data analysis, the study reveals that Indonesia’s downstreaming strategy does exemplify a new developmental state model, as the government does not aim just to stimulate economic growth but also to contribute to the energy transition with EV battery manufacturing and to invigorate social inclusion by ameliorating inequality particularly in Eastern Indonesia. Nevertheless, the application of the new developmental state model through the downstreaming strategy uncovers some areas where improvement is necessary. The policy needs to be continuously refined so that its negative environmental and social externalities can be mitigated, and it can serve as a better example of a new developmental state model.